The Role And The Formal Requirements Of Powers Of Attorney At Trial Before The Administrative Court - Andi Muhammad Ali Rahman (Prophetic Law Review, 2020)
This study aims to determine the role of the special power of attorney in trials before the Administrative Court and to determine the formal requirements of making a special power of attorney in the administrative court. The benefits of this research are legal philosophyt and scientific development, especially in the field of procedural law, as well as to become an additional reference for those who are interested in researching this problem further. In addition, this research is expected to provide input for the community, students, and legal practitioners.This study uses normative legal approach or commonly called doctrinal research approach, including statutes and cases. The results of this study provide two conclusions: First, the role of special power of attorney in the trial at the Administrative Court is also applicable the principle of not having to use a power or legal aid. The use of mentoring or representation, authorization, legal aid is a right and not an obligation of a person. Such use is an obligation of the state when a citizen requires it but is unable to obtain it for themselves. Second, matters related to the formal requirements to become a special power of attorney in the Administrative Court have been spelled out in the Administrative Technical Guidelines and the Technical of Civil Service Arbitration Tribunal, Book II, edition 2009, the Supreme Court of the Republic of Indonesia.